Factors Affecting the Perception of Insufficient Breast Milk Among Breastfeeding Mothers - Maria Winny Inez; Marleni Marleni (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: The coverage of exclusive breastfeeding in Indonesia has not yet reached the national target of 80%, despite a gradual increase over recent years. One of the main barriers to successful exclusive breastfeeding is the Perception of Insufficient Breast Milk (PIM), a psychological condition in which mothers believe that their breast milk production is inadequate to meet their infants’ needs. Purpose: To analyze factors associated with the perception of insufficient breast milk among breastfeeding mothers. Metdod: This study employed a quantitative analytic design with a cross-sectional approach. A total of 63 breastfeeding mothers who met the inclusion criteria were selected using purposive sampling. Data were collected using a structured questionnaire and analyzed using the Chi-square test with a significance level of α = 0.05. Results: The results showed that 57.1% of respondents experienced the perception of insufficient breast milk. Significant associations were found between maternal knowledge (p = 0.004; POR = 4.750), employment status (p = 0.014; POR = 0.256), family support (p = 0.007; POR = 4.202), and exposure to formula milk (p = 0.031; POR = 3.520) with the perception of insufficient breast milk. Support from health workers was not significantly associated with this perception (p = 0.303). Conclusion: Poor maternal knowledge, maternal employment, low family support, and exposure to formula milk contribute to an increased perception of insufficient breast milk. Continuous breastfeeding education, optimal family involvement, and stricter supervision of formula milk promotion are essential to strengthen mothers’ confidence in breastfeeding and to improve exclusive breastfeeding achievement.